ANALISIS PENGARUH KUALITAS PELAYANAN DAN EKUITAS MEREK TERHADAP LOYALITAS PELANGGAN - Anne Sandy Tobing; Ngatindriatun Ngatindriatun (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2019)
This study aim to analyze service quality and brand equity towards customer loyalty. A total 261 patients of ASIH maternity hospital were taken as samples using the convenience sampling method. Multiple linear regression analysis was used to analyze data in this study. The results showed that service quality and brand equity were have positive and significant effect to the loyalty of Asih maternity hospital customers. Adjusted R2 value is 0.169 which means that 16.9% of customer loyalty in RSB Asih can be explaned by service quality factors and brand equity. Therefore, to increase customer loyalty, take a policy that can improve service quality by providing training for employees in serving patients